2000
DOI: 10.1523/jneurosci.20-02-00806.2000
|View full text |Cite
|
Sign up to set email alerts
|

GABACReceptors Control Adaptive Changes in a Glycinergic Inhibitory Pathway in Salamander Retina

Abstract: We studied the role of GABA in adaptive changes in a lateral inhibitory system in the tiger salamander retina. In darkadapted retinal slice preparations picrotoxin caused a slow enhancement of glycine-mediated IPSCs in ganglion cells. The enhancement of glycinergic IPSCs developed slowly over the course of 5-20 min, even though picrotoxin blocked both GABA A and GABA C receptors within a few seconds. The slow enhancement of glycinergic IPSCs by picrotoxin was much weaker in light-adapted preparations. The slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…The spatial antagonism of glycinergic cells by GABAergic cells is also consistent with previous reports of serial inhibitory influences on ganglion-cell light responses in amphibian retina (Zhang et al, 1997;Cook et al, 2000). Of course, the interpretation of neurotransmitter antagonist effects in serial inhibition is very complex.…”
Section: Gabaergic Modulation Of the Glycinergic Mechanismsupporting
confidence: 89%
“…The spatial antagonism of glycinergic cells by GABAergic cells is also consistent with previous reports of serial inhibitory influences on ganglion-cell light responses in amphibian retina (Zhang et al, 1997;Cook et al, 2000). Of course, the interpretation of neurotransmitter antagonist effects in serial inhibition is very complex.…”
Section: Gabaergic Modulation Of the Glycinergic Mechanismsupporting
confidence: 89%
“…Blocking GABAergic inhibition with picrotoxin can cause an increase in glycinergic inhibition in dark-adapted tiger salamander retina (Cook et al, 2000). We tested to see whether the ineffectiveness of picrotoxin and TTX in blocking the primate parasol cell surround was attributable to an increase in glycinergic inhibition by applying a mixture that contained both picrotoxin and the glycine antagonist strychnine (100 M picrotoxin plus 0.5 M TTX plus 5 M strychnine, n ϭ 1 ONcenter cell, n ϭ 1 OFF-center cell; 100 M picrotoxin plus 0.5 M TTX plus 2 M strychnine plus 10 M I4AA, n ϭ 2 ONcenter cells).…”
Section: Application Of Drug Mixturesmentioning
confidence: 99%
“…Because blocking GABA A R inhibition with BIC only reduced but did not eliminate the inhibitory effects of NO on GLY release, most notably in the INL, it is possible that GABA A R inhibition was not the only pathway by which NO inhibits glycinergic neurons. GABA C Rs are predominantly located on bipolar cell axon terminals (Vitanova et al, 2001), and GABA C Rs have been shown to interact with glycinergic neurons (Cook et al, 2000). Enhanced feedback inhibition onto bipolar cells through GABA C R may reduce the excitatory drive to glycinergic neurons, resulting in reduced GLY release.…”
Section: No Inhibits Glycine Release Through the Modulation Of Gaba Rmentioning
confidence: 99%